International Fragmentation of Production and the Labour Input into Germany's Exports – An Input-Output-Analysis - Hans-Ulrich Brautzsch; Udo Ludwig (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2011)
The import penetration of exports has become a topic of public debate, particularly in the context of Germany's position as one of the world's leading exporters. The growth in the volume of intermediate products purchased from abroad for subsequent processing into export goods in Germany seems to be undermining the importance of exports as a driver of domestic production and employment. The gains that arise from an increase in exports seem to have been offset by the losses caused by the crowding out of local production by imports. Empirical evidence on the impact of this international integration of the goods market on the German labour market is ambiguous. Short-term negative effects on employment are claimed to be offset by the long-term benefit that the jobs lost in the short run will eventually be replaced by higher-skilled jobs with better perspectives. Against this background, the following hypothesis is tested empirically: Germany is poor in natural resources, but rich in skilled labour. In line with the Heckscher- Ohlin theory, Germany should therefore specialize in the production of export goods and services that are relatively intensive in these factors and should import those goods and services that are relatively intensive in unskilled labour ... – – Die Importdurchdringung der Exporte ist im Zusammenhang mit der Stellung Deutschlands als Exportweltmeister in der Öffentlichkeit diskutiert worden. Durch den wachsenden Zukauf von Vorleistungsgütern aus dem Ausland zur Weiterverarbeitung zu Exportgütern in Deutschland werde die Bedeutung des Exports als Motor von Produktion und Beschäftigung im Inland untergraben. Der Wohlfahrtsgewinn aus der Intensivierung des Exports würde durch Wohlfahrtsverluste infolge der Verdrängung einheimischer Produktion durch Importe erkauft. Die empirische Evidenz für die Wirkungen der internationalen Integration der Gütermärkte auf den deutschen Arbeitsmarkt ist jedoch nicht eindeutig. Negativen Folgen auf Beschäftigung und Einkommen in der kurzen Frist stehen Vorteile gegenüber, wenn die wegfallenden Arbeitsplätze durch höherwertige mit besseren Einkommensperspektiven ersetzt werden. Vor diesem Hintergrund wird folgende Hypothese getestet: Deutschland ist gering ausgestattet mit Rohstoffen, aber reichlich mit qualifizierter Arbeit. Gemäß der Heckscher-Ohlin-Theorie sollte sich Deutschland deshalb im Export auf die Produktion von qualifikationsintensiven Gütern spezialisieren und solche Güter importieren, die viel unqualifizierte Arbeit enthalten ...
urn:nbn:de:101:1-201112215393
Keywords: C67; F14; F16; 330; international trade; labour and skills market interactions; input-outputmodels; Außenhandel; Arbeitsmärkte; Qualifikation; Input-Output-Modelle